Mechano-catalysis boosts glycolaldehyde conversion to tetroses over a new Zn-COF catalyst. (14th December 2022) - Yang, Junxia; Fang, Xu; Ren, Guoqing; Yu, Tie
Abstract : This work reports a new Zn-COF with a three-dimension framework, which presents superior ability toward glycolaldehyde conversion to tetroses under mechano-catalysis conditions. Abstract : In this communication, we report a new covalent organic framework (COF) material, Zn-COF, and estimated its catalytic performance on higher sugar generation from glycolaldehyde through the formose reaction. The results confirmed that Zn-COF presented highest reaction efficiency under mechano-catalysis conditions with 62.7% glycolaldehyde conversion in 2 h and a normalized reaction rate ( R g ) of 31.35 × 10 −4 mol h −1 g −1 .